25.0k views
1 vote
Drag the tiles to the boxes to form correct pairs. (please help)

Match the pairs of equivalent expressions.

Drag the tiles to the boxes to form correct pairs. (please help) Match the pairs of-example-1
User HuyLe
by
5.1k points

1 Answer

3 votes

Answer:

Explanation:

1).
(4t-(8)/(5))-(3-(4)/(3)t)=(4t+(4)/(3)t)+(-(8)/(5)-3)


=((12)/(3)t+(4)/(3)t)-((8)/(5)+(15)/(5))


=(16)/(3)t-(23)/(5)

2). 7t - 22

3). 5(2t + 1) + (-7t + 28) = 10t + 5 - 7t + 28

= (10t - 7t) + 33

= 3t + 33

4).
(16)/(3)t-(23)/(5)

5).
(-(9)/(2)t+3)+((7)/(4)t+33)=(-(9)/(2)t+(7)/(4)t)+(3+33)


=(-(18)/(4)t+(7)/(4)t)+36


=((-18+7)/(4))t+36


=-(11)/(4)t+36

6).
-(11)/(4)t+36

7). 3(3t - 4) - (2t + 10) = 9t - 12 - 2t - 10

= (9t - 2t) - ( 12 + 10)

= 7t - 22

8). 3t + 33

Therefore, equivalent expressions are,

a).
(4t-(8)/(5))-(3-(4)/(3)t)=(16)/(3)t-(23)/(5)

b). 7t - 22 = 3(3t - 4) - (2t + 10)

c).
(-(9)/(2)t+3)+((7)/(4)t+33)=-(11)/(4)t+36

d). 5(2t + 1) + (-7t + 28) = 3t + 33

User Charisa
by
4.9k points